The Effect of Giving Soursop Leaf Decoction to Hypertension Patients at the Elderly Social Home - Sasono Mardiono; Andre Utama Saputra; Rizqi Febriansyah (Lentera Perawat, 2024)
Hypertension is a condition where a person experiences an abnormal increase in blood pressure in systole and diastole. There are many ways to lower blood pressure, one of which is with soursop leaf decoction water. The purpose of this study was to determine the effect of soursop leaf decoction water on lowering blood pressure in patients with hypertension at Harapan Harapan Kita nursing home, Palembang city. This study used a one group pre-test post-test pre-experimental design. The sample in this study were 33 people with hypertension in our hope nursing home Palembang city. With purposive sampling technique. This study was conducted for 8 weeks with 2 times the administration of Soursop leaf decoction water. The data analysis used is the Paired Sample T test. The instruments in this study used SOP (standard operating procedures) observation sheets for measuring blood pressure Sphygmomanometer, and stethoscope. The results of this study indicate that the administration of soursop leaf decoction water has an effect on systole blood pressure values with a P-Value = 0.000 and diastole blood pressure values P-Value = 0.001 so it can be concluded that there is an effect of soursop leaf decoction water on lowering blood pressure in elderly people with hypertension. The results of this study indicate that soursop leaf cooking water can reduce blood pressure in people with hypertension. Because of the content of antioxidants, potassium ions, which can lower blood pressure in soursop leaves.